Construction and experimental verification of user-friendly molecular subtypes mediated by immune-associated genes in hepatocellular carcinoma - Yuan, Juzheng; Wang, Yang; Wang, Xudan; Zhang, Wenjie; Ding, Rui; Yue, Shuqiang; Li, Xiao (Frontiers in Oncology, 2022)
Hepatocellular carcinoma (HCC) is the third leading cause of cancer death worldwide, and its prognosis remains poor even with the advent of many new technologies. The advent of immunotherapy seems to offer new hope, but low response rates are an unresolved problem. To investigate the role of immune-related genes in HCC, we analyzed the correlation between immune-related genes and the immune microenvironment in HCC through the HCC transcriptome dataset. The study also aimed to construct and experimentally validate user-friendly molecular subtypes mediated by immune-related genes in HCC. There are different immune cell infiltration patterns in HCC adjacent non-tumor tissues and tumor tissues. Patients with HCC could be classified into 2 subtypes: subtype A and subtype B. Specifically, subtype A shows characteristics of a hot tumor, in which the infiltration of antigen-presenting cells and the expression of other important immune-related factors are higher than in a cold tumor. In addition, we identified Hub genes for the different subtypes and constructed a prognostic prediction model based on six genes (KLRB1, KLF2, S100A9, MSC, ANXA5, and IMPDH1). Further experimental analysis of HCC samples showed that the expression levels of KLF2 and ANXA5 were associated with immune cell infiltration and expression of PD-L1 in tumor tissues. Our work suggests that the expression of immune-related genes plays an important role in the tumor microenvironment and prognosis of HCC patients and may be associated with immunotherapeutic response, which provides new clues for the widespread and effective application of immunotherapy in HCC.